Justice and Equality: The Endless Question (Universitas Negeri Semarang, 2022)
The discourse on justice and equality is not only a concern for Indonesia but also for the global context. Justice and equality are understood in various contexts, both in relation to where justice and equality are applied, when and to whom. But basically, justice and equality have the same goal, which is to ensure that everyone feels safe and gets the same treatment without discriminating against anything.